2018
DOI: 10.1097/ico.0000000000001533
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Histone H3 Acetylation and Chromatin Remodeling in Corneas of Alloxan-Induced Diabetic Rats

Abstract: The results of this study show that alloxan-induced diabetes altered the histone H3 acetylation pattern and compromised the chromatin supraorganization in corneal tissue/cells. Continued research is needed to understand the clinical and morphofunctional significance of changes in corneal cell nuclei of diabetic individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Interactions between INSR and the voltage-dependent anion channel-1 (VDAC1) prevent fragmentation and altered polarization of mitochondria, as well as facilitate PINK-1-mediated mitophagy [ 22 ]. In diabetic rats, the process of histone H3 acetylation is reduced in corneal epithelial cells, resulting in compacted chromatin organization in nuclei characterized by increased size and elevated DNA ploidy [ 48 ].…”
Section: The Role Of Insulin and Effect Of Diabetesmentioning
confidence: 99%
“…Interactions between INSR and the voltage-dependent anion channel-1 (VDAC1) prevent fragmentation and altered polarization of mitochondria, as well as facilitate PINK-1-mediated mitophagy [ 22 ]. In diabetic rats, the process of histone H3 acetylation is reduced in corneal epithelial cells, resulting in compacted chromatin organization in nuclei characterized by increased size and elevated DNA ploidy [ 48 ].…”
Section: The Role Of Insulin and Effect Of Diabetesmentioning
confidence: 99%
“…In addition, in a rat model of type I diabetes (utilizing alloxan induction), Herencia-Bueno et al (2018) found diabetes reduced histone H3 acetylation in the cornea, leading to aberrant chromatin organization 58 . Further research is needed to elucidate the implication of this change in corneas of patients with diabetes.…”
Section: Histone Modification and Granular Corneal Dystrophy And Othementioning
confidence: 99%